KAJIAN ELEMEN VISUAL ARSITEKTUR TERKAIT PERSEPSI ANAK USIA DINI TERHADAP BANGUNAN - Astrid Austranti Yuwono (Ide dan Dialog Desain Indonesia (Idealog), 2019)
Architecture is intended for users with long-term consideration.An architecture is a work of art that does not only belong to the creator of the work but also involves other people, users and observers.Early age in a human growth process is an important phase that needs special attention. It is also called as The Golden Age. One type of perception that has an important role in a child's growth period is visual perception.Through visual perception, a child learns to see differences, similarities, and groupings. The building is the result of the realization of an analysis of users, functions and ideas. Toddlersisone of the users who need special attention. Designer's understanding of what is needed by an early childandhow a child's perspectivein seeing their environment arestill not fully addressed. This study examines architectural elementsthat have more dominant role to be considered by toddlerswith the basis of perception theory. The method used in relation to respondents who are toddlersis to describe buildings based on their respective perceptionsby drawing. The results obtained in this study isthat the architectural elementsthat can be re-perceived by the respondent clearly are the shape and dimensions.